BS EN 61300-2-33. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Part 2-33. Tests. Assembly and disassembly of fibre optic mechanical splices, fibre management systems and protective housings (8th October 2021) - British Standards Institution,
No abstract available